Lewis-acid catalyzed N-acyliminium ion cyclodimerization: synthesis of symmetrical 1, 4-dioxanes. Issue 9 (25th February 2015) - Ali, Bakhat; Zukerman-Schpector, Julio; Ferreira, Fernando P.; Shamim, Anwar; Pimenta, Daniel C.; Stefani, Hélio A.
Graphical abstract: Abstract: The cyclodimerization reaction of N -substituted-5-hydroxy-pyrrolydinones promoted by BF3 ·Et2 O and HCl to obtain symmetrical 1, 4-dioxane derivatives was achieved in moderate to good yields, mild conditions, and short reaction times. These transformations render a promising alternative route that provides access to diverse 1, 4-dioxane derivatives with a wide structural diversity.